Religion and the imperial body politic of Japan. (24th July 2022) - Winfield, Pamela D
Abstract : This article offers a religious history of the Japanese emperor's body as it was discursively constructed, visually imagined, and ritually reinforced as the larger body politic. It demonstrates that the Shinto-inflected notion of the imperial body politic (J. kokutai) technically only emerged during the early modern period in Japan. It therefore draws attention instead to the important premodern Buddhist precursors that first equated the emperor's own body with the greater state polity of Japan. Buddhist teachings about the world-body of Buddhahood (dharmakaya), the monumental bronze Buddha body of Birushana in Nara, and Buddhist ritual activity throughout Japan's provincial temple system all helped to construct Emperor Shomu (r. 710–56) as the all-protecting head of the family-state (kokka). Later esoteric Buddhist teachings about 'becoming a Buddha in this very body' (sokushin jobutsu) and elaborate state-protecting rites performed before Kukai's (744–835) multi-headed and multi-armed figures all helped to protect the body of the emperor (or his clothes), and by extension, the health and wellbeing of the country at large. Finally, modern reformulations such as Kiyozawa Manshi's (1863–1903) 'hand metaphor' and Minobe Tatsukichi's (1873–1948) 'organ theory of government' continued to resonate with these pre-existing Buddhist corporeal tropes, as well as with newly imported Western philosophical constructs. As a result, this premodern Buddhist analysis of the emperor's rhetorical, artistic, and ceremonial body-state demonstrates the centrality of the human body in imagining religious authority and political power in Japan.